(3MSf GdXf HGddg YR hLds - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3YeQ Hf eMeOHf Ye GdJcQjJi s)
(3ChdgG (B:s
(3CNHQfG GdTjN CHh GdaVd eMeO Hf fGUQ GdSdGei bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd bHd ehJg HKdGK (B: (3dGjehJf CMOce EdG hgh jMSf GdXf HGddg YR hLd s
(3BNQgG (B:s
(3Yf GdfHi Udi Gddg Ydjg hSde bGd (B: (3Ef ddg YR hLd YJbGA ef GdfGQ ai cd jhe hdjdI , hdcd YHO efge OYhI eSJLGHI s
(3GdfSNI HgG MhGTs
(3HBNQ cd LRA YOI SeGYGJ fajSI hHBNQ GdLRA GdKGfi RjGOI HYV CHjGJ ef fSNI CNQi OGNdI ai GdSeGYs
(3cJHJ HNW bdjd GdfbW s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds